2019
DOI: 10.1039/c9ra03248g
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of nanoparticle formation and hazardous air pollutants emitted by 3D printer operations: from emission to inhalation

Abstract: Nanoparticle and HAP emissions from 3D printers and their deposition behavior in the human respiratory system were evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 41 publications
4
34
0
Order By: Relevance
“…The authors quantified and characterized VOC emissions of two commercial 3D printer filaments (ABS-CNT nanocomposite, ABS) in simulated FFF thermal conditions. In agreement with other studies [92] [80], styrene was found to comprise the highest fraction of total VOC emissions. The authors report that printing a few hundred grams of filament can result in the 1mg/m 3 IRIS reference concentration for inhalation exposure for styrene being exceeded, depending on room size and ventilation.…”
Section: Development Of Ventilation Recommendations Determination Ofsupporting
confidence: 92%
See 1 more Smart Citation
“…The authors quantified and characterized VOC emissions of two commercial 3D printer filaments (ABS-CNT nanocomposite, ABS) in simulated FFF thermal conditions. In agreement with other studies [92] [80], styrene was found to comprise the highest fraction of total VOC emissions. The authors report that printing a few hundred grams of filament can result in the 1mg/m 3 IRIS reference concentration for inhalation exposure for styrene being exceeded, depending on room size and ventilation.…”
Section: Development Of Ventilation Recommendations Determination Ofsupporting
confidence: 92%
“…In a recent study, Youn et al [92] Rao et al [93] used nanofiber-based air filters to collect PM2.5 particles (particles that have a diameter of less than 2.5 μm) generated from the function of a FFF printer, using ABS filament material. The authors suggest that the generation and aggregation of the particles is manifested in four stages.…”
Section: Quantifying Fff Emissionsmentioning
confidence: 99%
“…Regarding particle deposition on the human respiratory system, it was assessed that larger numbers of nanoparticles are deposited in the lower respiratory tract compared to the upper respiratory tract. According to these results, the nanoparticles deposit in the pulmonary region which consists primarily of alveolar airways [92].…”
Section: Assessment and Characterisation Of The Emissionsmentioning
confidence: 89%
“…In a recent study, Youn et al [92] performed an investigation of FFF emissions, measuring and sampling airborne nanoparticles and hazardous air pollutants at a 3D printing centre employing five FFF 3D printers utilizing PLA filament feedstock. The authors tested sequential and simultaneous use of the five printers, and also estimated emitted nanoparticle deposition in sectors of the respiratory system in the event of human exposure.…”
Section: Assessment and Characterisation Of The Emissionsmentioning
confidence: 99%
See 1 more Smart Citation